2020
DOI: 10.3390/en13153994
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study to Identify the Hindrances to Widespread Adoption of Electric Vehicles in Qatar

Abstract: The adoption of electric vehicles (EVs) have proven to be a crucial factor to decreasing the emission of greenhouse gases (GHG) into the atmosphere. However, there are various hurdles that impede people from purchasing EVs. For example, long charging time, short driving range, cost and insufficient charging infrastructures available, etc. This article reports the public perception of EV-adoption using statistical analyses and proposes some recommendations for improving EV-adoption in Qatar. User perspectives o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Research in [41], [42], [43], [44], [45], [46], [47], [48], and [49] found that the daily driving rage of countries like India, America, Finland, Denmark, and Norway were below 50 km. These shows that the current EV technology is well capable to fulfill users daily driving range requirement.…”
Section: A Driving Rangementioning
confidence: 99%
“…Research in [41], [42], [43], [44], [45], [46], [47], [48], and [49] found that the daily driving rage of countries like India, America, Finland, Denmark, and Norway were below 50 km. These shows that the current EV technology is well capable to fulfill users daily driving range requirement.…”
Section: A Driving Rangementioning
confidence: 99%
“…This group covers data related to driving behavior into the QU campus. In general, most of the population in Qatar has an average driving distance (round trip) of 40-100 km (2-3 hours) [25]. The number of students, faculty, and staff is 25,067 [24].…”
Section: ) Driving Behavior Data (Dataset-a)mentioning
confidence: 99%
“…Factors such as long charging hours, short driving range, cost, and other hindrances limit the use of electric vehicles in Qatar as well as other nations. According to Khandakar et al [33], they introduced a public perception that will motivate EV adoption in Qatar. Their study emphasized the different perspectives of EV adoption while engaging in direct questionnaires with electric vehicle stakeholders in the attempt to develop and improve on their requests to solve the various challenges limiting the adoption of EVs.…”
Section: Decarbonization In Mobility: the Tale Of Qatarmentioning
confidence: 99%